(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
High cholesterol levels in adolescents closely relate to coronary heart disease. Our study analyzes how body mass index (BMI), fat intake, and protein intake affect total cholesterol levels in adolescents. We collect BMI data through anthropometric measurements, fat and protein intake through 24-hour food recall analysis, and total cholesterol levels through lipid panel measurements in blood samples from 62 adolescents aged 17-19. Our t-test and chi-square test on the collected data reveal that while BMI significantly affects the total cholesterol levels (p-value = 0.04), fat and protein intake does not. These findings suggest that efforts to control the total cholesterol levels in adolescents should look more broadly at the overall dietary patterns rather than only at their fat and protein intake.